2020
DOI: 10.1542/peds.2020-0079
|View full text |Cite
|
Sign up to set email alerts
|

Transmitted Home Oximetry and Duration of Home Oxygen in Premature Infants

Abstract: OBJECTIVES:To determine if a home oxygen therapy (HOT) management strategy that includes analysis of recorded home oximetry (RHO) data, compared with standard monthly clinic visit assessments, reduces duration of HOT without harm in premature infants. METHODS:The RHO trial was an unmasked randomized clinical trial conducted in 9 US medical centers from November 2013 to December 2017, with follow-up to February 2019. Preterm infants with birth gestation #37 1 0/7 weeks, discharged on HOT, and attending their fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…The RHO trial was a randomized, unmasked, multi‐center trial in nine United States academic medical centers from November 2013 to December 2017, with follow‐up until February 2019 19 . The primary aim was to determine whether a HOT management strategy including analysis of RHO data, compared with standard of care monthly in‐clinic assessments with a PSG to discontinue HOT, reduced duration of HOT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RHO trial was a randomized, unmasked, multi‐center trial in nine United States academic medical centers from November 2013 to December 2017, with follow‐up until February 2019 19 . The primary aim was to determine whether a HOT management strategy including analysis of RHO data, compared with standard of care monthly in‐clinic assessments with a PSG to discontinue HOT, reduced duration of HOT.…”
Section: Methodsmentioning
confidence: 99%
“…The recorded home oximetry (RHO) trial was the first multi‐center, randomized control trial to evaluate any structured HOT management strategies in preterm infants on HOT 19,20 . The intervention included the use of RHO to help manage and titrate flow rates between standard monthly clinic visits.…”
Section: Introductionmentioning
confidence: 99%
“…Infants treated with supplemental oxygen at home had marginally improved growth but no improvement in developmental outcomes at 2 years corrected age. Recorded home oximetry facilitates weaning from supplemental home oxygen but impacts on development are unknown 65,66 . Tracheostomy is the definitive treatment to support long‐term mechanical ventilation in infants with BPD.…”
Section: Influence Of Strategies To Prevent or Treat Bpd On Developmental Outcomesmentioning
confidence: 99%
“…Importantly, structured weaning targeting oxygen saturation levels within recommended ranges has been demonstrated to reduce the duration of oxygen supplementation with the rate of weaning being more rapid in those infants having more regular episodes of continuous saturation monitoring [42]. Active weaning and a shorter home oxygen duration treatment is associated with enhanced parental quality of life [43].…”
Section: Neurodevelopmental Outcomementioning
confidence: 99%
“…Ongoing titration studies should be undertaken. Weaning can be achieved on an approximately monthly basis [42,45] and ideally more frequently [43]. A previous, similar structured programme has demonstrated that infants can be weaned more rapidly from oxygen without adverse outcomes [62] (Fig.…”
mentioning
confidence: 99%